ANTONOV WETTING LINE PHASE TRANSITION OF TWO-COMPONENT BOSE-EINSTEIN CONDENSATES UNDER CONSTRAINT OF ROBIN BOUNDARY CONDITION - Nguyễn Văn Thụ; Hoàng Văn Quyết (Tạp chí Khoa học Đại học Đà Lạt)
Using double Parabola approximation, in this paper, after finding the wave function for the ground state, we found an analytical relation for wetting phase transition and Antonov line of two-component Bose-Einstein condensates. The Robin boundary condition was applied for our system. Based on these results, we reobtained results for our system with constraint by Dirichlet boundary condition.